Dimension and morphological variation of the sella turcica in Libyan adults in Benghazi using CT scan - Hani, Rodina; Karwad, Mustafa; Haidar, Murshed (Benghazi University Medical Journal, 2024)
Background: The sella turcica is a significant anatomical structure used to assess sellar and parasellar pathologies, as well as in orthodontic procedures. Normal sellar anatomy varies significantly between different populations. Currently, there is insufficient knowledge about the sella turcica among the Libyan community. Aim: The aim of this study is to evaluate and assess the correlation between sellar dimensions and morphological variants with gender. Results: Data from computed tomography of 146 Libyan adults (66 females and 80 males) aged from 18 to 70 years was analyzed using SPSS. The mean length, depth, and anteroposterior diameter were 9.924±2.001mm, 8.575±1.651mm, and 12.502±1.912mm, respectively. The round shape was the most common, found in 54.8% of subjects, followed by oval (32.2%) and flattened (13%). When assessing whether gender plays a role in the size and shape of the sella turcica, there was no statistically significant difference between males and females in relation to all sellar measurements and shapes. Conclusion: The results of this study can be used as a reference standard for the Libyan population in various medical specialties, including radiology, neurosurgery, forensic medicine, and orthodontics. This can aid in the early diagnosis of pathologies, leading to better management and follow-up. Additionally, the findings can serve as a basis for further international research investigations.